Plasmon-assisted Energy Transfer near Coated Metal Cylinders - Bradley, Louise (My University, 2013)
In this contribution we consider the decay and energy transfer rates of dipole emitters near dielectric-coated metal cylinders. The surface plasmons excited at the surface of the metal core can act as a very efficient channel both for increasing the decay rate of the emitter or for the transfer of energy from one dipole to another
Proceedings of 5th International Conference on Transparent Optical Networks (ICTON)
5th International Conference on Transparent Optical Networks (ICTON)
PUBLISHED
Keywords: coated metal cylinder; decay rates; surface plasmons; energy transfer